Table of Content - - (Journal of Humanities & Social Sciences, 2023)
Table of Content: 1. The Saudi family’s use of smart applications to plan its affairs and its impact on the quality of family and social interaction in the year 2021-2022 Rasha Saud Zakour 2. Importance of the Total Quality in the Social Institutions Sharefa Saad Alqriny, Amani Ali Albishi 3. The Impact of Internet on Research -A Case Study on Master Students at Economics & Administration College in King Abdul-Aziz University Rawia Reda Obaid, Hind Ahmed Alamoudi, Ghaidaa Sultan Alreheli, Lujain Asad Abu Rizaiza 4. Interactive map of historical and archaeological sites in Makkah Almukarama Athmar AbdulMohsen Alamri 5. Rumors across social platforms from perception of anchors and journalists in the kingdom of Jordan post Covid-19 pandemic Ahmed Rasheed Bani Odeh 6. Issues Encountered during the Translation Process Dr. Ahmed Mohamed Lemine El-Mokhtar 7. Issues of Translating Financial Terms: Equivalence at the Word Level and Collocation level (Arabic-English) Dr. Hamdi Abdelrasool Alje’eam